Molecular tools in genetic breeding of Megathyrsus maximus for semiarid region: a review (Research, Society and Development, 2020)
The need to have food available to the herd, throughout the year, generates efforts to develop methods and techniques to adapt tropical forages to regions with water deficit. In this perspective, the objective of this research was to carry out a literature review on forage grasses of the species Megathyrsus maximus and molecular tools for its improvement, in view of the adaptation capacity of the species to the Brazilian semiarid environment. To this end, information was obtained through publications in national and international databases, intellectual property databases and agencies with cultivar protection. The results achieved were favorable, in terms of characteristics, productive potential and resilience of forages of the genus Megathyrsus. Studies are suggested in order to select a species with a high tolerance potential to water deficit, through adaptation, persistence and high mass production, aided by molecular markers to complement and optimize the agronomic information that takes into account the climate-soil-plant relationship.